Evaluasi Kompentensi Profesional Mahasiswa dalam Melaksanakan PPLK Jurusan Teknik Elektro Universitas Negeri Padang - Singgih Prayogi; Hastuti Hastuti (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
The research conducted on PLK students majoring in electrical engineering is research that aims to find out the various problems when students majoring in electrical engineering carry out PPLK and what things need to be improved by PLK students related to their professional teaching competence during PPLK. which uses the Goal Oriented Evaluation Model evaluation model developed by Tyler with a population of 30 students majoring in electrical engineering who have implemented PPLK. Research procedures, namely 1). Perform evaluation plan preparation, 2). Perform data verification 3). Processing and analyzing data 4). Provide Interpretation and Draw Conclusions. Data collection using questionnaires and documentation. Data analysis used data verification and quantitative analysis. The results of this study indicate that the evaluation study of students majoring in electrical engineering PPLK on the professional competence of teaching is in accordance with the competence of teaching and is good enough. It was concluded that the teaching professional competence of students majoring in electrical engineering PPLK according to student assessments, when viewed from the professional competence of teaching with the achievement of degrees of 82.062% is in the good category in supporting the achievement of PPLK goals.